Effects of Untreated and Treated Rice Husk Ash (RHA) on Physical Properties of Recycled Aluminium Chip AA7075 - Mohd Joharudin, Nurul Farahin; Abdul Latif, Noradila; Mustapa, Mohammad Sukri; Badarulzaman, Nur Azam (International Journal of Integrated Engineering, 2020)
The use of low cost metal matrix composites (MMC) is increasing rapidly in various engineering fields because of their better mechanical properties. The effects of recycled aluminium chips AA7075 with untreated rice husk ash (URHA) and treated rice husk ash (TRHA) on physical properties were investigated. Recycled aluminium chip AA7075 was reinforced with untreated and treated rice husk ash i.e., 2.5 wt.%, 5 wt.%, 7.5 wt.%, 10 wt.% and 12.5 wt.%. Density, apparent porosity, water absorption, micro-hardness and microstructures analysis of the metal matrix composites samples were examined in current study. The density for metal matrix composites increase up to 5 wt.% of rice husk ash, and then decreased with increasing mass fraction of rice husk ash. However, the densities for treated rice husk ash slightly higher than untreated rice husk ash. Porosity and water absorption of metal matrix composites were consistently increase at increasing mass fraction of rice husk ash. The hardness of chip AA7075 has improved with increasing the composition of rice husk ash from 53.49 Hv to 65.93 Hv for untreated rice husk ash and 69.56 Hv for treated rice husk ash at addition 10 wt.%. The microstructures of metal matrix composites were found random distribution and non-homogeneous compared to fully chip AA7075.